2022
DOI: 10.1186/s13063-021-05914-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Buyang Huanwu granules and Naoxintong capsules in the treatment of stable angina pectoris: rationale and design of a randomized, blinded, multicentre clinical trial

Abstract: Background Stable angina pectoris (SAP) currently seriously threatens the health of humans, and mortality is continuously rising. Current treatment strategies mainly include pharmaceutical therapy and revascularization. In China, Buyang Huanwu granules (BYHW) and Naoxintong capsules (NXT) have been used in the treatment of SAP, but it is not clear which agent is better in terms of relieving symptoms and improving quality of life. Therefore, we designed a clinical trial to compare the efficacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…CSA, characterized by chest pain or discomfort, is a major symptomatic presentation in about 50% of patients with CHD ( Gao et al, 2021 ). In China, the prevalence rate of CSA was about 3.6% in 2017 and the numbers are still rapidly increasing in recent years due to ageing as well as multiple risk factors such as diabetes mellitus, hypertension, etc., ( Wang et al, 2022 ). Currently, guideline-directed therapy for CSA mainly includes antiplatelet agents, statins, calcium channel blockers and nitrates ( Healthcare Engineering, 2023 ).…”
Section: Clinical Researchmentioning
confidence: 99%
“…CSA, characterized by chest pain or discomfort, is a major symptomatic presentation in about 50% of patients with CHD ( Gao et al, 2021 ). In China, the prevalence rate of CSA was about 3.6% in 2017 and the numbers are still rapidly increasing in recent years due to ageing as well as multiple risk factors such as diabetes mellitus, hypertension, etc., ( Wang et al, 2022 ). Currently, guideline-directed therapy for CSA mainly includes antiplatelet agents, statins, calcium channel blockers and nitrates ( Healthcare Engineering, 2023 ).…”
Section: Clinical Researchmentioning
confidence: 99%
“…Relevant clinical studies and meta-analysis have proved that its therapeutic effect on stable angina pectoris (SAP)and stroke ( Zhang et al, 1995 ; Gao et al, 2021 ; Wang et al, 2022a ). Recently, Wang et al (2022b) designed a randomized, blinded, parallel controlled, multicenter clinical trial to compare the efficacy and safety of NXT and BYHW in the treatment of SAP. The results of the trial have yet to be published.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…[9–11] It consists of 2 types: stable and unstable angina. [12,13] According to theory of traditional Chinese medicine (TCM), AP belongs to the “ Xiong Bi ,” “chest arthralgia,” and “heartache.” Its major pathogenesis is explained by “heart pulse stasis” and “Qi statsis.” [14–20] Clinical practice has proven that Yangxin Decoction (YXD) has unique advantages for the management of patients with AP of CHD. [21–29]…”
Section: Introductionmentioning
confidence: 99%
“…Its major pathogenesis is explained by "heart pulse stasis" and "Qi statsis." [14][15][16][17][18][19][20] Clinical practice has proven that Yangxin Decoction (YXD) has unique advantages for the management of patients with AP of CHD. [21][22][23][24][25][26][27][28][29] Previous studies have reported that YXD can improve the AP of CHD by increasing the levels of serum 6-Keto-PGF 1α, high-density lipoprotein cholesterol, and apolipoprotein A.…”
Section: Introductionmentioning
confidence: 99%